Converting organosulfur compounds to inorganic polysulfides against resistant bacterial infections - Zhuobin Xu (Nature Portfolio, 2018)
Garlic has a mild antibacterial activity due to its organosulfur content. Here, the authors develop an approach to convert natural organosulfur into iron-sulfur nanosheets, with significantly higher antibacterial activity that can be used against infections as well as biofilms.